Bibliography and the information society - Capaccioni, Andrea (Bibliothecae.it, 2021)
The paper offers reflection on the contribution that bibliography can offer to the information society. In recent decades, the role of information has become decisive not only as regards the cultural but also economic aspects of society. With the spread of the Internet, a general rethinking of information organization became indispensable. In this new scenario, the bibliography can play an important role in the context of recorded communication.